Transcriptional profiling of zebrafish intestines identifies macrophages as host cells for human norovirus infection - Emma Roux; Reegan J. Willms; Jana Van Dycke; Álvaro Cortes Calabuig; Lore Van Espen; Geert Schoofs; Jelle Matthijnssens; Johan Neyts; Peter de Witte; Edan Foley; Joana Rocha-Pereira (Gut Microbes)
Human noroviruses (HuNoVs) are a major cause of diarrheal disease, yet critical aspects of their biology, including cellular tropism, remain unclear. Although research has traditionally focused on the intestinal epithelium, the hypothesis that HuNoV infects macrophages has been recurrently discussed and is investigated here using a zebrafish larval model. Through single-cell RNA sequencing of dissected zebrafish intestines, we unbiasedly identified macrophages as host cells for HuNoV replication, with all three open reading frames mapped to individual macrophages. Notably, HuNoV preferentially infects actively phagocytosing inflammatory macrophages. HuNoV capsid proteins and double-stranded RNA colocalized within intestinal macrophages of infected zebrafish larvae, and the negative-strand RNA intermediate was detected within FACS-sorted macrophages. Flow cytometry confirmed viral replication within these macrophages, constituting approximately 23% of HuNoV’s host cells. Identifying macrophages as host cells prompts a reevaluation of their role in HuNoV pathogenesis, offering new directions for understanding and controlling this infection.